Beyond the state: reconceptualising African security in the 21st century. Issue 1 (2nd January 2017) - Solomon, Hussein
ABSTRACT: Confronted with myriad security challenges, African states and the much-vaunted peace and security architecture of the African Union (AU) has proven not to be up to the challenge. Indeed, this is implicitly acknowledged by the AU itself if one considers the creation of such security structures as the African Mission in Somalia (AMISOM), which exists outside its peace and security architecture. This paper argues for a radical rethink of security structures on the African continent – one in which state structures of security coexist with newer forms of security actors, including private military companies (PMCs), community movements and the business sector. Whilst this shift in security actors is already happening on the ground, policymakers need to embrace this new reality.